2022
DOI: 10.3390/ijms23116179
|View full text |Cite
|
Sign up to set email alerts
|

Omega-6 Polyunsaturated Fatty Acids Enhance Tumor Aggressiveness in Experimental Lung Cancer Model: Important Role of Oxylipins

Abstract: Lung cancer is currently the leading cause of cancer death worldwide; it is often diagnosed at an advanced stage and bears poor prognosis. It has been shown that diet is an important environmental factor that contributes to the risk and mortality of several types of cancers. Intake of ω-3 and ω-6 PUFAs plays an important role in cancer risk and progression. Current Western populations have high consumption of ω-6 PUFAs with a ratio of ω-6/ω-3 PUFAs at 15:1 to 16.7:1 This high consumption of ω-6 PUFAs is relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 85 publications
1
10
0
Order By: Relevance
“…Additionally, as a single-center retrospective analytical study, conducting a prospective multicenter study would enhance our comprehensive understanding of the association between FAPs and the risk of DN. Despite these limitations, our findings align with previous research and suggest potential intervention measures for preventing DN [14, 30‒33].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, as a single-center retrospective analytical study, conducting a prospective multicenter study would enhance our comprehensive understanding of the association between FAPs and the risk of DN. Despite these limitations, our findings align with previous research and suggest potential intervention measures for preventing DN [14, 30‒33].…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the oil yields from this study presented ALA (0.96%) at similar levels compared with fish oil (1.45%) which is considered an omega-3-rich oil [ 45 , 46 ]. Furthermore, it was demonstrated that administration of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), which is an obesogenic-related ligand of the AHR, in omega-3 fatty acids-fed mice reduced the growth rates of lung carcinoma-derived tumors and inhibited their metastasis to lung and liver [ 47 , 48 ]. This could suggest that omega-3 fatty acids could attenuate AHR activation and lead to other beneficial health effects.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, PUFA are known to induce proliferation, apoptosis and angiogenesis [ 150 ]. However, their role in metastasis is still in its infancy due to the lack of experimental models which adequately recapitulate the complexity of human cancer, but recently, the intake of ω-6 PUFAs in the diet was shown to enhance the malignancy of tumor cells by the upregulation of pro-tumoral oxylipins (PGs, HETEs, DiHETrEs and HODEs) in a murine model of pulmonary squamous cell carcinoma, increasing proliferation, angiogenesis and molecular aggressiveness [ 151 ]. Increased oxylipin metabolism was also proposed as a marker for the evaluation of early stage of breast cancer [ 152 ].…”
Section: Metabolic Plasticitymentioning
confidence: 99%